2022
DOI: 10.3390/genes13111920
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Oocyte Maturation Defects and Early Embryo Development Arrest

Abstract: Various pathogenic factors can lead to oogenesis failure and seriously affect both female reproductive health and fertility. Genetic factors play an important role in folliculogenesis and oocyte maturation but still need to be clarified. Oocyte maturation is a well-organized complex process, regulated by a large number of genes. Pathogenic variants in these genes as well as aneuploidy, defects in mitochondrial genome, and other genetic and epigenetic factors can result in unexplained infertility, early pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…Previous studies have reported several genes associated with the pathogenesis of oocyte maturation arrest (TUBB8, PATL2) and fertilization failures (TLE6, WEE2). [56]. In this study, seven polymorphisms were selected from four hormone-related genes (FSHR rs6165, INHA rs11893842 and rs35118453, ESR1 rs9340799 and rs2234693, BMP15 rs1700321, and rs3810682), and the association between RIF occurrence and polymorphisms was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported several genes associated with the pathogenesis of oocyte maturation arrest (TUBB8, PATL2) and fertilization failures (TLE6, WEE2). [56]. In this study, seven polymorphisms were selected from four hormone-related genes (FSHR rs6165, INHA rs11893842 and rs35118453, ESR1 rs9340799 and rs2234693, BMP15 rs1700321, and rs3810682), and the association between RIF occurrence and polymorphisms was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these conventional epigenetic modifications, chromatin architecture and the RNA m 6 A modification are recently founded to be dynamically regulated during MZT 27,28 . In addition, epigenetic reprogramming defects can cause developmental defects and reproductive problems 29–33 . Deciphering how and why this process occurs during early embryogenesis is crucial for addressing reproduction problems.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 In addition, epigenetic reprogramming defects can cause developmental defects and reproductive problems. 29 , 30 , 31 , 32 , 33 Deciphering how and why this process occurs during early embryogenesis is crucial for addressing reproduction problems. However, constrained by scarcity of mammalian early embryos and technical limitations, global reprogramming of the epigenetic landscape during MZT and precise regulatory network of this complex process remain enigmatic for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte maturation is closely related to early embryonic development. Failure of oocyte maturation will seriously affect both female reproductive health and fertility [ 1 ]. Increasing studies have shown that abnormal oocyte maturation leads to fertilization failure, embryo development retardation, and embryo death before implantation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%